Highly selective Diels–Alder and Heck arylation reactions in a divergent synthesis of isoindolo- and pyrrolo-fused polycyclic indoles from 2-formylpyrrole - Escalante, Carlos H.; Martínez-Mora, Eder I.; Espinoza-Hicks, Carlos; Camacho-Dávila, Alejandro A.; Ramos-Morales, Fernando R.; Delgado, Francisco; Tamariz, Joaquín (Beilstein Journal of Organic Chemistry, 2020)
A highly regio-, chemo- and stereoselective divergent synthesis of isoindolo- and pyrrolo-fused polycyclic indoles is herein described, starting from 2-formylpyrrole and employing Diels–Alder and Heck arylation reactions. 3-(N-Benzyl-2-pyrrolyl)acrylates and 4-(pyrrol-2-yl)butenones underwent a highly endo-Diels–Alder cycloaddition with maleimides to furnish octahydropyrrolo[3,4-e]indoles, which served as precursors in the regioselective synthesis of aza-polycyclic skeletons via an intramolecular Heck arylation reaction. Through the latter reaction, the 3-(N-benzyl-2-pyrrolyl)acrylates give rise to 3-(pyrrolo[2,1-a]isoindol-3-yl)acrylates. A further oxidative aromatization of the polycyclic intermediates provides the corresponding polycyclic pyrrolo-isoindoles and isoindolo-pyrrolo-indoles. A theoretical study on the stereoselective Diels–Alder reactions, carried out by calculating the endo/exo transition states, revealed the assistance of non-covalent interactions in governing the endo stereocontrol.
Keywords: endo-Diels–Alder stereocontrol; 2-formylpyrrole; intramolecular Heck arylation reaction; non-covalent interactions; pyrroloindoles; pyrroloisoindoles